Microbial synthesis of chalcogenide semiconductor nanoparticles: a review. Issue 1 (25th June 2015) - Jacob, Jaya Mary; Lens, Piet N. L.; Balakrishnan, Raj Mohan
Summary: Chalcogenide semiconductor quantum dots are emerging as promising nanomaterials due to their size tunable optoelectronic properties. The commercial synthesis and their subsequent integration for practical uses have, however, been contorted largely due to the toxicity and cost issues associated with the present chemical synthesis protocols. Accordingly, there is an immediate need to develop alternative environment‐friendly synthesis procedures. Microbial factories hold immense potential to achieve this objective. Over the past few years, bacteria, fungi and yeasts have been experimented with as eco‐friendly and cost‐effective tools for the biosynthesis of semiconductor quantum dots. This review provides a detailed overview about the production of chalcogen‐based semiconductor quantum particles using the inherent microbial machinery. Abstract : Lead and cadmium based chalcogenide semiconductor quantum dots are valued for their size tunable optical properties. The present review detail the green biosynthesis routes initiated for the synthesis of these technologically relevant counterparts.